Electrophoretic deposition of TiO2 and SrTiO3nanoparticles as photo-electrocatalyst for water splitting / Phoon Bao Lee - Phoon , Bao Lee (2018)
Fossil fuels are currently the most economical sources for H2 production. Nonetheless, these processes would cause greenhouse gases (GHG) emission that may lead to certain environmental issues such as climate change and global warming. Photocatalytic water splitting was commonly used for H2 production but the efficiency tends to be low. This main issue is the dispersion of powdered photocatalyst during the photocatalysis reaction which will cause (i) lower yield due to backward reaction of the intermediates, (ii) poor optical response due to the light scattering effects, and (iii) poor reusability due to the post-filtration. In this study, the photocatalyst was coated on a thin film for photoelectrochemical (PEC) water splitting under UV light irradiation. The TiO2 was successfully and uniformly coated on fluorine doped tin oxide (FTO) glass by electrophoretic deposition (EPD) technique. The effect of several parameters such as deposition voltage, time, and post heat treatment temperature have been studied in order to produce a high smoothness TiO2 layer for better PEC performance. The EPD technique is capable for tuning the smoothness and thickness of TiO2. From FESEM image, the nanocrystalline TiO2 with the film thickness of 14.6 μm gives a good uniformity and minimal cracking surface. The optimum condition to form TiO2 thin film is 30 V, 60 s, and heat treatment at 400 oC. This film exhibited the highest hydrogen production rate and photoconversion efficiency (PCE) of 0.40 mL cm-2 h-1 and 2.49%, respectively. This demonstrated that the EPD technique is very promising to be used to coat TiO2 on FTO glass for PEC water splitting. In the case of perovskite SrTiO3, the morphology of SrTiO3 nanoparticle was significantly influenced by the hydrothermal temperature. The best photocatalytic activity of SrTiO3 in PEC performance was synthesised at 150 oC. This is due to uniform particle size, shape, and large specific surface area. By fabricating the SrTiO3 on the thin films using EPD technique, the optimum condition was found to be 40 V and 120 s. Based on the FESEM image, SrTiO3 film with the thickness of 18.8 μm exhibited the highest photocurrent density of 1.05 mA/cm2. The immobilised SrTiO3 is capable for generating 0.25 mL cm-2 h-1 of H2 and the PCE was found to be 1.28% under UV light irradiation. It is interesting to observe that the efficiency of TiO2 was much better than that of SrTiO3. The plausible reasons were as follows, (i) the specific surface area of TiO2 is 3.3 times larger, and (ii) the particle size of TiO2 is 2 times smaller as compared to that of SrTiO3.